Nasal Polyposis and Serum Albumin: Systemic Effects of Local Inflammation - Sousa-Machado, André (2023)
Introduction The genesis of chronic rhinosinusitis is always a topic of debate. A polyp is a pale, edematous tissue emerging mostly from the middle meatus. An epithelial injury caused by continuous inflammation of the nasal mucosa is considered to be a possible cause of the genesis of nasosinusal polyps. Objective To understand the link between serum albumin levels and nasal polyposis. Methods A retrospective study of 180 consecutive patients between January 2016 and January 2020 at our center. We then divided the patients into three age- and gender-matched groups: 60 patients with chronic rhinosinusitis with nasal polyposis, 60 patients with chronic rhinosinusitis without nasal polyposis, and a control group with 60 patients. No patient had a history of any pathology that could alter serum albumin. We then compared the level of serum albumin between the three groups. Results The group of patients with rhinosinusitis and nasal polyposis consisted of 60 patients with a serum albumin value of 4.49 ± 0.29 g/dL, whereas in the control group, the serum albumin value was 4.67 ± 0.2 g/dL. We found a significant difference between the group with nasal polyposis and the other two groups evaluated: chronic rhinosinusitis without nasal polyposis (p<0.001) and the control group (p<0.001). Conclusions Lower levels of serum albumin can be seen in patients with chronic rhinosinusitis with nasal polyposis. Further studies should aim to apply its value since it is a non-expensive marker, to the follow-up of those patients or even to stratify them according to their endotype.